Variasi Musiman Tinggi Gelombang Laut di Perairan Pulau Enggano Provinsi Bengkulu - Chinci, Jeniu; Lizalidiawati, Lizalidiawati; Suhendra, Suhendra; Anjasman, Anjasman (Universitas Bengkulu, 2024)
Enggano Island is one of Indonesia's outermost islands located in the waters west of Sumatra. Enggano Island is directly adjacent to the vast and deep Indian Ocean so that the waters are very dynamic. One of them is known that the sea waves in these waters are very volatile. This study aims to find out the seasonal variation of sea wave height in the waters of Enggano Island, Bengkulu Province. This study uses primary data in the form of sea wave height measured at Kaana Beach and secondary data for 3 years (2021-2023) in the form of monthly average wind direction and speed, temperature and density data obtained from https://data.marine. copernicus.eu/viewer/expert?view=layers&dataset=GLOBAL_ANALYSISFORECAST_PHY_001_024, sea wave height data obtained from https://data.marine.copernicus. eu/viewer/expert?view=layers&dataset=GLOBAL_ANALYSISFORECAST_WAV_001_027. Data processing uses Python Anaconda 3 software for 2D display and Microsoft Excel for time series display. The methods used in this study are descriptive and quantitative methods. The results of the study show that the sea wave height in the waters of Enggano Island varies seasonally, it can be seen that the maximum sea wave height occurs in the eastern season in August with a value of 1.5-3 m with a wind direction and speed of 5-6 m/s and 7 m/s in the southern area of the island, while the minimum wave height occurs in the western season in December with a value of 1-2 m with a wind direction and speed of 1-2 m/s blowing towards the North and West of the island. Keywords : Enggano Island, seasonal variation, high sea waves, wind speed